Evaluating the Impact of Employment Protection on Firm-Provided Training in an RDD Framework - Thomas Bolli; Johanna Kemper (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper exploits exceptions in the application of employment protection legislation (EPL) to small firms beneath a particular size threshold to test the theoretical hypothesis that EPL increases the incentives of firms to train their employees in a regression discontinuity setting. Using firm-level data from Finland and Italy provides no empirical evidence for this hypothesis. In fact, the results rather suggest a potentially negative impact, which is unstable across empirical specifications though. We test whether this might be due to a negative selection of employees by comparing firms with low and high shares of old employees. The insignificantly higher effect of EPL for firms with older workers provides at best suggestive evidence that EPL affects training negatively though.
Keywords: J24; J21; L51; 330